High energy efficient clock synchronization protocol for sensor networks using time division flooding - ZENG Yi; HU Bo; FENG Hui (Tongxin xuebao)
In most synchronization protocols that based on classic flooding scheme,the arrival time of packets couldn’t be predicted,so nodes had to keep monitoring the channel.Therefore,idle listening was quite serious which leaded to low energy efficiency.A novel synchronization protocol focusing on reducing idle listening was proposed,where time division flooding scheme was adopted to spread messages.Unique transmitting and receiving slots would be assigned to each individual in localized and distributed way.Higher energy efficiency,lower clock compensation error and faster convergence speed could be achieved,as shown in the simulations.Furthermore,it could be easily modified to co-work with plenty of MAC protocols.